Determination of EC50 Values for Cu, Zn, and Cr on Microorganisms Activity in a Mediterranean Sandy Soil. Issue 12 (4th January 2018) - Carabassa, Vicenç; Domene, Xavier; Ortiz, Oriol; Marks, Evan A. N.; Alcañiz, Josep M.
Abstract: Ecotoxicity of three potentially toxic metals (PTM) (Cu, Zn, and Cr) in a slightly acidic sandy soil is tested using the soil respiration test (OECD‐217) in order to determine EC50 values for the carbon transformation activity of microorganisms. Addition of an organic amendment of Populus leaves is also crossed with metal spiking in order to investigate possible interaction with metal toxicity. Soil respiration is measured at day 1 and 28 after the soil spiking with the PTM to assess short‐term effects on soil microbial activity. Of the three metals tested, Cu shows the highest toxicity at the longest exposure times (day 28) and Zn shows a strong inhibitory effect in the short‐term (day 1), even though later toxicity diminish significantly. Cr is the least toxic studied PTM. Organic amendment outweighs any adverse effects of these metals, increasing soil respiration, even in the treatments with high doses of metals. Abstract : Ecotoxicity of Cu, Zn, and Cr in a slightly acidic sandy soil is tested using the soil respiration test in order to determine EC50 values for the carbon transformation activity of microorganisms. Cu shows the highest toxicity at the longest exposure times (day 28) and Zn shows a strong inhibitory effect in the short‐term (day 1), even though later toxicity diminish significantly.